2020
DOI: 10.1021/acsnano.0c02593
|View full text |Cite
|
Sign up to set email alerts
|

Se-Rich MoSe2 Nanosheets and Their Superior Electrocatalytic Performance for Hydrogen Evolution Reaction

Abstract: Two-dimensional MoSe2 has emerged as a promising electrocatalyst for the hydrogen evolution reaction (HER), although its catalytic activity needs to be further improved. Herein, we report Se-rich MoSe2 nanosheets synthesized using a hydrothermal reaction, displaying much enhanced HER performance at the Se/Mo ratio of 2.3. The transition from the 2H to the 1T′ phase occurred as Se/Mo exceeded 2. Structural analysis revealed the presence of Se adatoms as well as the formation of Se–Se bonding. Based on first-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(94 citation statements)
references
References 55 publications
1
93
0
Order By: Relevance
“…To fabricate the Z-scheme heterostructure, the primary premise is the matching band structure, in which the conduction band of one semiconductor should locate as close to the valence band of another semiconductor as possible. It is reported that the conduction band potential of MoSe 2 (about −0.45 eV 25 ) is lower than the conduction band of ZnIn 2 S 4 , but very close to its valence band (0.99 eV 9 ), which suggests that the photogenerated electrons in the conduction band of MoSe 2 are likely to recombine with the photogenerated holes in the valence band of ZnIn 2 S 4 following Z-scheme pathway. However, as known from the current literatures, MoSe 2 can only play the role of cocatalyst in ZnIn 2 S 4 /MoSe 2 instead of realizing Z-scheme charge transfer 26,27 .…”
mentioning
confidence: 98%
“…To fabricate the Z-scheme heterostructure, the primary premise is the matching band structure, in which the conduction band of one semiconductor should locate as close to the valence band of another semiconductor as possible. It is reported that the conduction band potential of MoSe 2 (about −0.45 eV 25 ) is lower than the conduction band of ZnIn 2 S 4 , but very close to its valence band (0.99 eV 9 ), which suggests that the photogenerated electrons in the conduction band of MoSe 2 are likely to recombine with the photogenerated holes in the valence band of ZnIn 2 S 4 following Z-scheme pathway. However, as known from the current literatures, MoSe 2 can only play the role of cocatalyst in ZnIn 2 S 4 /MoSe 2 instead of realizing Z-scheme charge transfer 26,27 .…”
mentioning
confidence: 98%
“…[ 19 ] To find suitable alternatives to Pt catalysts, researchers studied a variety of nonprecious metals catalysts. [ 20,21 ] Relevant researchers used cyclic voltammetry to sequence the catalytic activities of some non‐noble metals, and the measurement results were Ni > Mo > Co > W > Fe > Cu. [ 22 ]…”
Section: Electrochemical Water Splitting Reaction Pathmentioning
confidence: 99%
“…Moreover, the doping of non-metallic atoms can change the crystalline phase of Mo-based materials, resulting in high catalytic activity. For example, Kwon and co-workers reported a non-stoichiometric Se-rich MoSe 2 synthesized by hydrothermal reaction [101]. When Se/Mo ratio exceeded two, the MoSe 2 changed from 2H to 1T' phase.…”
Section: Heteroatomic Dopingmentioning
confidence: 99%